Measurement of sediment yield under different field conditions using drop box weir with coshocton wheel - ATHIRA S; Kala K. S; Nidhi S. S; Er. Sasikala D (Guide) (Tavanur 2005 Kelappaji College of Agricultural Engineering and Technology)
Measurement of sediment yield under different field conditions using drop box weir with coshocton wheel
Measurement of sediment yield under different field conditions using drop box weir with coshocton wheel